High‐performance liquid chromatography/electrospray ionisation mass spectrometric characterisation of metabolites produced by Pseudovibrio sp. W64, a marine sponge derived bacterium isolated from Irish waters. (6th September 2018) - Choudhary, Alka; Naughton, Lynn M.; Dobson, Alan D.W.; Rai, Dilip K.
Abstract : Rationale: In recent years, metabolites produced by Pseudovibrio species have gained scientific attention due to their potent antimicrobial activity. Recently, we also have assessed the antibacterial activities of Pseudovibrio sp. W64 isolates against Staphylococcus aureus, where only the dominant tropodithietic acid (TDA) was identified. However, characterisation of other metabolites is necessary as these metabolites may also serve as potent antimicrobial agents. Methods: Liquid chromatography/tandem mass spectrometry (LC/MS/MS), aided by accurate mass measurements, was employed to screen and characterise a range of metabolites produced by Pseudovibrio sp. W64 via assessment of ethyl acetate fractions generated from bacterial cultures. Results: Thirteen metabolites unique to the bacterial culture were detected and their chemical structures were assigned by MS/MS and accurate mass measurements. Among the thirteen metabolites, a methyl ester of TDA, a number of cholic acid derivatives, and amino diols and triols were characterised. Conclusions: Pseudovibrio sp. W64 produces methylated TDA in addition to TDA, and metabolises lipids and amino acids in the cell‐culture medium. To the best of our knowledge, this is the first report of methylated TDA, cholic acid and its various analogs, and sphinganine being detected in this Pseudovibrio strain. The data generated may help to better understand the biochemical processes and metabolism of bacterial strains towards discovery of antimicrobial agents from marine sources.